Rediscovery of Tomosomus Motschulsky, 1855 (Coleoptera: Anthicidae) with redescription of the genus, a new genus-rank synonym, and a key to species - Telnov, Dmitry; Gusakov, Alexey A. (Zootaxa, 2023)
Tomosomus Motschulsky, 1855, an obscure incertae sedis genus of Anthicidae erroneously considered monotypic, was found to be congeneric with the tomoderine genus Holcopyge Champion, 1890. A new genus-rank synonym (Tomosomus Motschulsky = Holcopyge Champion syn. nov.) and two new combinations are proposed for the species hitherto attributed to Holcopyge. Tomosomus subtestaceus Motschulsky, 1855, the type of its genus, is redescribed from rediscovered type material and recently collected specimens. An annotated checklist, key to species and new records of Tomosomus are provided.